Traditional use and qualitative chemical composition of medicinal plants in the communities of Sardinata and Cúcuta in Norte de Santander - Colombia - Ascanio, Erika Andrea; Chaves-Bedoya, Giovanni; Ortiz-Rojas, Luz Yineth (Sociedad Colombiana de Ciencias Hortícolas-SCCH and Universidad Pedagógica y Tecnológica de Colombia-UPTC, 2023)
Traditional medicine is part of the culture of the people, it is an expression of intangible cultural heritage that combines different traditional knowledge and practices. Medicinal plants have been used as an alternative method to conventional medicine, and their use in developing countries has been inherited generationally. The aim of this study was to determine the prevalence of use in traditional medicine and preliminary identification of secondary metabolites present in medicinal plants used for the treatment of ailments in two municipalities from Norte de Santander-Colombia. The research method used for the development of the project is qualitative and experimental. Interviews were conducted with 40 herbalists in the markets of the municipalities of Sardinata and Cúcuta. Experimentally, the ethanolic extract of 17 medicinal plants was obtained to identify the secondary metabolites present using the technique of thin layer chromatography (TLC). The results suggests that the secondary metabolites of higher prevalence in the most used medicinal plants are flavonoids and terpenes. Information gained from traditional and medicinal plants maintains an important cultural value and represents an alternative use for the management of ailments at low cost, highlighting the importance of phytotherapy for communities. The results of the study not only confirm the relevance of medicinal plants in the region, but also highlight the importance of continuing to research and document the applications and benefits of these plants in traditional and modern medicine.